Water: Impacts of plastic pollution on human health and biological systems - Bello, Yusuf Samaila (FLORONA : Jurnal Ilmiah Kesehatan, 2025)
Current spare of human development consisting of advancements in science and technology that led to the synthesis of plastics, polymers with diverse benefits in human endeavours; and on the other hand, the need for quality water is more intensified nowadays. Plastics pollution is rising due to mismanagement, and inturn causing contamination of water bodies and ultimately affecting biological systems. A review of literatures pertaining water, plastics and water pollution was done to fulfill the objective of this study. This study examines the harmful effects of plastics in water on human health and biological systems. Plastics, widely used in daily life, contaminate water sources, posing significant health risks. This review explores the role of water in biological systems, types of plastics, sources of plastic pollution, harmful chemicals conveyed by plastics, and management strategies.This paper concludes that behavior change, effective waste management, effective water supply and treatment, awareness creation may contribute greatly in controlling water pollution caused by plastic pollution.